Sustainability of territorial systems in the context of economic indicators - Novoseltseva, G. B.; Palatkin, I. V.; Rasskazova, N. V. (Modernizat͡s︡ii͡a︡, innovat͡s︡ii, razvitie, 2023)
Purpose: of the study is to identify factors and parameters that provide opportunities for sustainable development for territorial systems (regions), based on the analysis of the dynamic series of key statistical indicators. Methods: the basis of the study is the use of various methodological approaches, systemic, multivariate analysis, methodology of institutional reforms. The research methodology is based on the systematization and comparative analysis of the main statistical indicators of the development of the economic and innovative spheres of the Volga Federal District and Russia as a whole, which ultimately makes it possible to identify the growth drivers of territorial systems. Results: the study analyzes the indicators of economic and innovative development of the subjects of the Volga Federal District and Russia. Based on this, four types of sustainability of territorial systems were identified: sustainability of the depressive type, sustainability of the adaptive type, sustainability of the advanced type, sustainability of the innovative type. The type of economic stability was determined for each subject of the region, which made it possible to identify drivers and growth points. In the context of rapidly changing external factors of development, the results obtained are relevant, since they allow us to determine the trajectory of the development of territorial systems. Conclusions and Relevance: economic and innovative indicators of development make it possible to classify the Volga Federal District as a region with an established adaptive type of stability. The drivers of the region's development are developed agriculture, industrial production, high-tech and innovative production. The positive dynamics of the socio-economic indicators of the region with a focus on innovative components ensures an increase in the degree of stability of the regional system. Activation of drivers and stimulation of growth points is the result of the strategy and implementation of socio-economic policy measures to achieve innovation-type sustainability in the region.